Phase difference film and method for manufacturing the same
By contacting the resin film of the crystalline polymer with organic solvent and adjusting the NZ coefficient of the phase difference film, the manufacturing problems in the prior art are solved, and a phase difference film with an NZ coefficient less than 1.0 and a small haze is achieved, which improves the Display quality of the display device.
Patent Information
- Application Number
- CN202080052256.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-31
- Filing Date
- 2020-07-02
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-07-02
AI Technical Summary
The prior art is difficult to manufacture a phase difference film with an NZ coefficient of less than 1.0 and a small haze, and the manufacturing method is complicated and control is difficult.
By using a resin film containing a crystalline polymer to contact the organic solvent, the birefringence in the thickness direction is changed, thereby adjusting the NZ coefficient and controlling the haze less than 1.0% during the process.
The manufacturing of a phase difference film with an NZ coefficient of less than 1.0 and a small haze is achieved, which simplifies the manufacturing process and improves the viewing angle, contrast and image quality of the display device.
Smart Images

Figure BDA0003477367750000251 
Figure BDA0003477367750000261
Abstract
Description
Technical Field
[0001] The present invention relates to a phase difference film and a method for manufacturing the same. Background Art
[0002] Conventionally, techniques for producing films using resins have been proposed (Patent Documents 1 to 3).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent document 1: Japanese Patent Application Laid-Open No. 02-64141.
[0006] Patent document 2: Japanese Patent Application Publication No. 2016-26909.
[0007] Patent document 3: International Publication No. 2017 / 065222. Summary of the invention
[0008] Problem that the invention aims to solve
[0009] A phase difference film is a type of film made of resin. A phase difference film has retardation in at least one of an in-plane direction and a thickness direction, and therefore, is generally required to have a large birefringence in at least one of the in-plane direction and the thickness direction.
[0010] The balance between the birefringence in the in-plane direction and the birefringence in the thickness direction can be expressed by the NZ coefficient. For example, if a retardation film with an NZ coefficient of less than 1.0 is obtained, the viewing angle, contrast, image quality and other display qualities of a display device can be improved by the retardation film.
[0011] The prior art is known to have a method for manufacturing a phase difference film with an NZ coefficient of less than 1.0. However, in the prior art manufacturing method, it is not possible to simply manufacture a phase difference film with an NZ coefficient of less than 1.0. For example, in the prior art manufacturing method, it is necessary to combine the stretching and shrinking of the film, or to use a multilayer film with a precisely adjusted thickness. Therefore, there is a tendency for the manufacturing method to become complicated, either because there are many control items or many processes.
[0012] In addition, since phase difference films are a type of optical film, they are usually required to have low haze. However, among phase difference films with an NZ coefficient of less than 1.0, especially phase difference films with low haze, it is difficult to manufacture them using existing technologies. Therefore, a technology for realizing phase difference films with an NZ coefficient of less than 1.0 and low haze is also needed, regardless of whether the manufacturing method is simple or not.
[0013] The present invention has been made in view of the above technical problems, and an object of the present invention is to provide a retardation film having an NZ coefficient of less than 1.0 and a small haze, and a method for easily manufacturing a retardation film having an NZ coefficient of less than 1.0.
[0014] Solutions for solving problems
[0015] The present inventors have conducted in-depth research to solve the above problems. As a result, the present inventors have found that a phase difference film with an NZ coefficient of less than 1.0 can be simply manufactured by the following method, which includes the following steps: a first step of preparing an optically isotropic resin film formed by a resin containing a crystalline polymer, and a second step of contacting the resin film with an organic solvent to change the birefringence in the thickness direction. Furthermore, the present inventors have found that by adopting this manufacturing method, a phase difference film with an NZ coefficient of less than 1.0 and a small haze can be achieved. Based on these insights, the present inventors have completed the present invention.
[0016] That is, the present invention includes the following contents.
[0017] [1] A phase difference film formed of a resin containing a crystalline polymer,
[0018] The NZ coefficient of the above-mentioned retardation film is less than 1.0, and
[0019] The retardation film has a haze of less than 1.0%.
[0020] [2] The retardation film according to [1], wherein an NZ coefficient of the retardation film is greater than 0.0 and less than 1.0.
[0021] [3] The retardation film according to [1] or [2], wherein the retardation film contains an organic solvent.
[0022] [4] The phase difference film according to [3], wherein the organic solvent is a hydrocarbon solvent.
[0023] [5] The phase difference film according to any one of [1] to [4], wherein the crystalline polymer contains an alicyclic structure.
[0024] [6] The phase difference film according to any one of [1] to [5], wherein the crystalline polymer is a hydrogenated product of a ring-opening polymer of dicyclopentadiene.
[0025] [7] A method for manufacturing a phase difference film, comprising the following steps:
[0026] In the first step, an optically isotropic resin film formed of a resin including a crystalline polymer is prepared, and
[0027] In the second step, the resin film is brought into contact with an organic solvent to change the birefringence in the thickness direction.
[0028] [8] The method for producing a phase difference film according to [7], further comprising, after the second step, a third step of stretching the resin film.
[0029] [9] The method for producing a retardation film according to [7] or [8], wherein the organic solvent is a hydrocarbon solvent.
[0030]
[10] The method for producing a retardation film according to any one of [7] to [9], wherein the crystalline polymer contains an alicyclic structure.
[0031]
[11] The method for producing a retardation film according to any one of [7] to
[10] , wherein the crystalline polymer is a hydrogenated product of a ring-opening polymer of dicyclopentadiene.
[0032] Effects of the Invention
[0033] According to the present invention, it is possible to provide a retardation film having an NZ coefficient of less than 1.0 and a small haze, and a method for easily producing a retardation film having an NZ coefficient of less than 1.0. DETAILED DESCRIPTION
[0034] The present invention will be described in detail below with reference to the embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and can be arbitrarily modified within the scope of the claims of the present invention and their equivalents.
[0035] In the following description, unless otherwise specified, the in-plane retardation Re of the film is a value represented by Re=(nx-ny)×d. In addition, unless otherwise specified, the birefringence in the in-plane direction of the film is a value represented by (nx-ny), and is therefore represented by Re / d. Furthermore, unless otherwise specified, the retardation Rth in the thickness direction of the film is a value represented by Rth=[{(nx+ny) / 2}-nz]×d. In addition, unless otherwise specified, the birefringence in the thickness direction of the film is a value represented by [{(nx+ny) / 2}-nz], and is therefore represented by Rth / d. Furthermore, unless otherwise specified, the NZ coefficient of the film is a value represented by (nx-nz) / (nx-ny). Here, nx represents the refractive index of the direction providing the maximum refractive index in the direction perpendicular to the thickness direction of the film (in-plane direction). Ny represents the refractive index in the direction orthogonal to the nx direction in the above-mentioned in-plane direction of the film. Nz represents the refractive index in the thickness direction of the film. d represents the thickness of the film. Unless otherwise stated, the measurement wavelength was 590 nm.
[0036] In the following description, unless otherwise specified, the material with positive intrinsic birefringence means a material with a refractive index in the stretching direction greater than the refractive index in the direction perpendicular thereto. In addition, unless otherwise specified, the material with negative intrinsic birefringence means a material with a refractive index in the stretching direction less than the refractive index in the direction perpendicular thereto. The value of intrinsic birefringence can be calculated based on the dielectric constant distribution.
[0037] In the following description, "long strip" refers to a film having a length of 5 times or more relative to the width, preferably a film having a length of 10 times or more, specifically, a film having a length that can be rolled up for storage or transportation. The upper limit of the length is not particularly limited, and is usually less than 100,000 times the width.
[0038] In the following description, unless otherwise specified, the directions of elements "parallel", "perpendicular", and "orthogonal" may include errors within a range that does not impair the effects of the present invention, for example, within a range of ±5°.
[0039] In the following description, the length direction of the long film is usually parallel to the film conveying direction in the production line. In addition, the MD direction (machine direction) is the film conveying direction in the production line, which is usually parallel to the length direction of the long film. Furthermore, the TD direction (transverse direction) is the direction parallel to the film surface and perpendicular to the above-mentioned MD direction, which is usually parallel to the width direction of the long film.
[0040] [1. Overview of Phase Difference Film of First Embodiment]
[0041] The phase difference film of the first embodiment of the present invention is formed of a resin containing a crystalline polymer, has an NZ coefficient of less than 1.0, and has a small haze. Such a phase difference film has not been realized in the prior art, but is realized for the first time by the present invention. The phase difference film can improve the clarity of the image displayed by the display device and improve the display quality such as viewing angle, contrast, and image quality by being arranged in, for example, a display device.
[0042] Technical means for solving the problem of improving the clarity of images displayed by display devices and improving display quality have been sought, but it is difficult to materialize the technical means. In one aspect, it can be said that the retardation film of the first embodiment realizes the materialization of the above-mentioned technical means for the first time.
[0043] [2. Crystalline resin contained in phase difference film]
[0044] The phase difference film of the first embodiment is formed by a resin containing a crystalline polymer. "Crystallizable polymer" means a polymer having a melting point Tm. That is, "crystallizable polymer" means a polymer whose melting point can be observed using a differential scanning calorimeter (DSC). In the following description, a polymer having crystallinity is sometimes referred to as a "crystalline polymer". In addition, a resin containing a crystalline polymer is sometimes referred to as a "crystalline resin". The crystalline resin is preferably a thermoplastic resin.
[0045] The crystalline polymer preferably has positive intrinsic birefringence. By using a crystalline polymer having positive intrinsic birefringence, a retardation film having an NZ coefficient of less than 1.0 can be easily produced.
[0046] The crystalline polymer preferably contains an alicyclic structure. By using a crystalline polymer containing an alicyclic structure, the phase difference film can have good mechanical properties, heat resistance, transparency, low hygroscopicity, dimensional stability and lightness. The polymer containing an alicyclic structure means a polymer having an alicyclic structure in the molecule. Such a polymer containing an alicyclic structure can be, for example, a polymer or a hydride thereof that can be obtained by a polymerization reaction using a cyclic olefin as a monomer.
[0047] As the alicyclic structure, for example, a cycloalkane structure and a cycloolefin structure can be cited. Among these, from the aspect of being easy to obtain a phase difference film with excellent characteristics such as thermal stability, a cycloalkane structure is preferred. The number of carbon atoms contained in one alicyclic structure is preferably 4 or more, more preferably 5 or more, preferably 30 or less, more preferably 20 or less, and particularly preferably 15 or less. By making the number of carbon atoms contained in one alicyclic structure within the above range, mechanical strength, heat resistance and formability can be highly balanced.
[0048] In the crystalline polymer containing an alicyclic structure, the ratio of the structural unit having an alicyclic structure to the total structural units is preferably 30% by weight or more, more preferably 50% by weight or more, and particularly preferably 70% by weight or more. By making the ratio of the structural unit having an alicyclic structure as large as described above, the heat resistance can be improved. The ratio of the structural unit having an alicyclic structure to the total structural units can be 100% by weight or less. In addition, in the crystalline polymer containing an alicyclic structure, there is no particular limitation on the remaining parts except the structural unit having an alicyclic structure, and it can be appropriately selected according to the purpose of use.
[0049] Examples of the crystalline polymer containing an alicyclic structure include the following polymers (α) to (δ). Among these, the polymer (β) is preferred because a retardation film having excellent heat resistance can be easily obtained.
[0050] Polymer (α): a crystalline polymer among ring-opening polymers of cyclic olefin monomers.
[0051] Polymer (β): a crystalline polymer among hydrogenated products of the polymer (α).
[0052] Polymer (γ): a crystalline polymer among addition polymers of cyclic olefin monomers.
[0053] Polymer (δ): a crystalline polymer among hydrogenated products of the polymer (γ).
[0054] Specifically, as the crystalline polymer containing an alicyclic structure, a crystalline polymer among ring-opening polymers of dicyclopentadiene and a crystalline polymer among hydrogenated products of ring-opening polymers of dicyclopentadiene are more preferred. Among them, a crystalline polymer among hydrogenated products of ring-opening polymers of dicyclopentadiene is particularly preferred. Here, the ring-opening polymer of dicyclopentadiene refers to a polymer in which the ratio of the structural unit derived from dicyclopentadiene to the total structural units is usually 50% by weight or more, preferably 70% by weight or more, more preferably 90% by weight or more, and further preferably 100% by weight.
[0055] The hydrogenated product of the ring-opening polymer of dicyclopentadiene preferably has a high proportion of syndiotactic diads. Specifically, the proportion of syndiotactic diads in the repeating units in the hydrogenated product of the ring-opening polymer of dicyclopentadiene is preferably 51% or more, more preferably 70% or more, and particularly preferably 85% or more. A high proportion of syndiotactic diads indicates high syndiotactic stereoregularity. Therefore, there is a tendency that the higher the proportion of syndiotactic diads, the higher the melting point of the hydrogenated product of the ring-opening polymer of dicyclopentadiene.
[0056] The ratio of the syndiotactic diad can be determined based on the following examples. 13 The results were confirmed by C-NMR spectroscopy analysis.
[0057] As the polymers (α) to (δ), polymers obtained by the production method disclosed in International Publication No. 2018 / 062067 can be used.
[0058] The melting point Tm of the crystalline polymer is preferably 200° C. or higher, more preferably 230° C. or higher, and preferably 290° C. or lower. By using a crystalline polymer having such a melting point Tm, a retardation film having a better balance between moldability and heat resistance can be obtained.
[0059] Generally, a crystalline polymer has a glass transition temperature Tg. The specific glass transition temperature Tg of the crystalline polymer is not particularly limited, but is generally 85°C or higher and generally 170°C or lower.
[0060] The glass transition temperature Tg and melting point Tm of a polymer can be measured by the following method. First, the polymer is melted by heating, and the melted polymer is quenched with dry ice. Next, the polymer can be used as a test body to measure the glass transition temperature Tg and melting point Tm of the polymer using a differential scanning calorimeter (DSC) at a heating rate of 10°C / min (heating mode).
[0061] The weight average molecular weight (Mw) of the crystalline polymer is preferably 1000 or more, more preferably 2000 or more, and preferably 1000000 or less, more preferably 500000 or less. A crystalline polymer having such a weight average molecular weight has an excellent balance between molding processability and heat resistance.
[0062] The molecular weight distribution (Mw / Mn) of the crystalline polymer is preferably 1.0 or more, more preferably 1.5 or more, and preferably 4.0 or less, more preferably 3.5 or less. Here, Mn represents the number average molecular weight. A crystalline polymer having such a molecular weight distribution has excellent molding processability.
[0063] The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the polymer can be measured as polystyrene-equivalent values by gel permeation chromatography (GPC) using tetrahydrofuran as an eluent.
[0064] The crystallinity of the crystalline polymer contained in the phase difference film is not particularly limited, and is usually higher than a certain degree. The specific range of crystallinity is preferably 10% or more, more preferably 15% or more, and particularly preferably 30% or more. The crystallinity of the crystalline polymer can be measured by X-ray diffraction.
[0065] The crystalline polymer may be used alone or in combination of two or more at any ratio.
[0066] The ratio of the crystalline polymer in the crystalline resin is preferably 50% by weight or more, more preferably 70% by weight or more, and particularly preferably 90% by weight or more. When the ratio of the crystalline polymer is above the lower limit of the above range, the birefringence and heat resistance of the phase difference film can be improved. The upper limit of the ratio of the crystalline polymer can be 100% by weight or less.
[0067] The crystalline resin may contain any component in addition to the crystalline polymer. Examples of the optional component include antioxidants such as phenolic antioxidants, phosphorus antioxidants, and sulfur antioxidants; light stabilizers such as hindered amine light stabilizers; waxes such as petroleum waxes, Fischer-Tropsch waxes, and polyalkylene waxes; nucleating agents such as sorbitol compounds, metal salts of organic phosphoric acids, metal salts of organic carboxylic acids, kaolin, and talc; diaminostilbene derivatives, coumarin derivatives, azole derivatives (e.g., benzophenones ... Fluorescent whitening agents such as oxazole derivatives, benzotriazole derivatives, benzimidazole derivatives and benzothiazole derivatives), carbazole derivatives, pyridine derivatives, naphthalene dicarboxylic acid derivatives and imidazole derivatives; UV absorbers such as benzophenone UV absorbers, salicylic acid UV absorbers and benzotriazole UV absorbers; inorganic fillers such as talc, silica, calcium carbonate and glass fiber; colorants; flame retardants; flame retardant aids; antistatic agents; plasticizers; near infrared absorbers; lubricants; fillers; and any polymers other than crystalline polymers such as soft polymers. Any component may be used alone or in combination of two or more in any ratio.
[0068] [3. NZ coefficient of retardation film]
[0069] The NZ coefficient of the retardation film of the first embodiment of the present invention is usually less than 1.0. When such a retardation film having an NZ coefficient less than 1.0 is provided in a display device, it can improve the display quality of the display device such as viewing angle, contrast, and image quality.
[0070] Depending on the purpose of the phase difference film, the specific value of the NZ coefficient of the phase difference film can be arbitrary, and can be, for example, less than 0.8, less than 0.6, less than 0.4, etc. The lower limit of the NZ coefficient of the phase difference film is arbitrary, and can be, for example, greater than -1000, greater than -500, greater than -100, greater than -40, greater than -20, etc. Among them, from the aspect that it is particularly difficult to manufacture using the existing technology, the NZ coefficient of the phase difference film is preferably greater than 0.0.
[0071] The NZ coefficient of a film can be obtained by calculation from the in-plane retardation Re and the retardation Rth in the thickness direction of the film.
[0072] [4. Haze of phase difference film]
[0073] The haze of the phase difference film of the first embodiment of the present invention is usually less than 1.0%, preferably less than 0.8%, more preferably less than 0.5%, and ideally 0.0%. When such a phase difference film with a small haze is provided in a display device, the clarity of the image displayed by the display device can be improved.
[0074] The haze of the film can be measured using a haze meter (for example, “NDH5000” manufactured by Nippon Denshoku Industries, Ltd.).
[0075] [5. Organic solvent contained in phase difference film]
[0076] The retardation film of the first embodiment of the present invention may contain an organic solvent. The organic solvent is usually added to the film in the second step of the production method described in the second embodiment.
[0077] All or part of the organic solvent added to the film in the second step can enter the interior of the polymer. Therefore, even if the organic solvent is dried above the boiling point, it is difficult to easily and completely remove the solvent. Therefore, the phase difference film usually contains an organic solvent.
[0078] As the above-mentioned organic solvent, an organic solvent that does not dissolve the crystalline polymer can be used. Preferred organic solvents include hydrocarbon solvents such as toluene, limonene, and decalin; and carbon disulfide. The type of organic solvent may be one or more.
[0079] The ratio of the organic solvent contained in the retardation film to 100% by weight of the retardation film (solvent content) is preferably 10% by weight or less, more preferably 5% by weight or less, and particularly preferably 0.1% by weight or less.
[0080] The solvent content of the retardation film can be measured by the measuring method described in the examples.
[0081] [6. Other characteristics of retardation film]
[0082] The retardation film generally has a large birefringence in at least one of the in-plane direction and the thickness direction. Specifically, the retardation film generally has a 1.0×10 -3 The in-plane birefringence Re / d and 1.0×10 -3 At least one of the absolute values of birefringence |Rth / d| in the thickness direction described above.
[0083] Specifically, the birefringence Re / d in the in-plane direction of the retardation film is usually 1.0×10 -3 Above, preferably 3.0×10 -3 Above, particularly preferably 5.0×10 -3 There is no upper limit, and it can be, for example, 2.0×10 -2 Below, 1.5×10 -2 Below, or 1.0×10 -2 However, the absolute value of birefringence |Rth / d| in the thickness direction of the retardation film is 1.0×10 -3 In the above case, the birefringence Re / d in the in-plane direction of the retardation film may be outside the above range.
[0084] The absolute value of birefringence in the thickness direction of the retardation film |Rth / d| is usually 1.0×10 -3 Above, preferably 3.0×10 -3 Above, particularly preferably 5.0×10 -3 There is no upper limit, and it can be, for example, 2.0×10 -2Below, 1.5×10 -2 Below, or 1.0×10 -2 However, the birefringence Re / d in the in-plane direction of the retardation film is 1.0×10 -3 In the above case, the absolute value of birefringence |Rth / d| in the thickness direction of the retardation film may be outside the above range.
[0085] The value of the in-plane retardation Re of the phase difference film can be set according to the application of the phase difference film.
[0086] The specific in-plane retardation Re of the phase difference film is preferably 10 nm or less, more preferably 5 nm or less, and particularly preferably 3 nm or less. In this case, the phase difference film can function as a positive C plate or a negative C plate.
[0087] In addition, the specific in-plane retardation Re of the phase difference film can be preferably 100 nm or more, more preferably 110 nm or more, particularly preferably 120 nm or more, and can be preferably 180 nm or less, more preferably 170 nm or less, particularly preferably 160 nm or less. In this case, the phase difference film can function as a quarter wave plate.
[0088] Furthermore, the specific in-plane retardation Re of the phase difference film can be preferably 245 nm or more, more preferably 265 nm or more, particularly preferably 270 nm or more, and can be preferably 320 nm or less, more preferably 300 nm or less, particularly preferably 295 nm or less. In this case, the phase difference film can function as a 1 / 2 wave plate.
[0089] The value of the retardation Rth in the thickness direction of the phase difference film can be set according to the purpose of the phase difference film. The specific retardation Rth in the thickness direction of the phase difference film can be preferably 200nm or more, more preferably 250nm or more, and particularly preferably 300nm or more. In addition, the upper limit can be 10000nm or less.
[0090] The retardation of the film can be measured using a phase difference meter (for example, "AxoScan OPMF-1" manufactured by AXOMETRICS CORPORATION).
[0091] The phase difference film is an optical film, so it is preferably highly transparent. The specific total light transmittance of the phase difference film is preferably 80% or more, more preferably 85% or more, and particularly preferably 88% or more. The total light transmittance of the phase difference film can be measured using an ultraviolet visible spectrophotometer in the range of wavelengths of 400nm to 700nm.
[0092] The thickness d of the phase difference film can be appropriately set according to the purpose of the phase difference film. The specific thickness d of the phase difference film is preferably 5 μm or more, more preferably 10 μm or more, particularly preferably 20 μm or more, preferably 200 μm or less, more preferably 100 μm or less, and particularly preferably 50 μm or less. When the thickness d of the phase difference film is above the lower limit of the above range, the operability can be good, or the strength can be improved. In addition, when the thickness d of the phase difference film is below the upper limit, the long phase difference film is easy to wind.
[0093] The phase difference film may be a single film or a long film.
[0094] The retardation film of the above-mentioned first embodiment can be produced by the production method described in the second embodiment to be described later.
[0095] [7. Overview of the method for producing a phase difference film according to the second embodiment]
[0096] The method for manufacturing a retardation film according to the second embodiment of the present invention includes the following steps: a first step of preparing an optically isotropic resin film formed of a crystalline resin containing a crystalline polymer, and a second step of contacting the resin film with an organic solvent to change the birefringence in the thickness direction. In this manufacturing method, the NZ coefficient of the resin film can be adjusted in the second step, so a retardation film having an NZ coefficient of less than 1.0 can be easily manufactured.
[0097] The present inventors speculate as follows about the mechanism by which a retardation film having an NZ coefficient of less than 1.0 can be obtained by this production method. However, the technical scope of the present invention is not limited to the following mechanism.
[0098] When the optically isotropic resin film formed of a crystalline resin is brought into contact with an organic solvent in the second step, the organic solvent penetrates into the resin film. Under the action of the penetrated organic solvent, the molecules of the crystalline polymer in the film undergo micro-Brownian motion, causing the molecular chains of the film to be oriented. According to the research of the inventors, it is believed that when the molecular chains are oriented, the solvent-induced crystallization phenomenon of the crystalline polymer can be promoted.
[0099] However, the surface area of the resin film is larger on the front and back surfaces as the main surfaces. Therefore, the penetration rate of the organic solvent is larger when the organic solvent penetrates into the thickness direction through the front or back surface. Then, the molecules of the crystalline polymer are oriented so that the molecules of the polymer are oriented in the thickness direction.
[0100] By orienting the molecules of the crystalline polymer in the thickness direction in this way, the NZ coefficient of the resin film can be adjusted. Thus, the resin film after contact with the organic solvent can be obtained as a phase difference film having an NZ coefficient of less than 1.0. The NZ coefficient can be adjusted by simply contacting the optically isotropic resin film with the organic solvent, which is useful in making the manufacture of the phase difference film easier.
[0101] The method for manufacturing a phase difference film of the second embodiment of the present invention may further include an arbitrary step to be combined with the above-mentioned first step and second step. For example, the method for manufacturing a phase difference film may include a third step of stretching the resin film after the second step, and may also include a fourth step of heat treating the resin film after the second step. When these arbitrary steps are implemented, a phase difference film can be obtained as a resin film whose properties are adjusted by these arbitrary steps.
[0102] [8. First step: Preparation of resin film]
[0103] In the first step, an optically isotropic resin film made of a crystalline resin containing a crystalline polymer is prepared. In the following description, the resin film before contacting with the organic solvent in the second step may be appropriately referred to as a "raw material film".
[0104] As for the crystalline resin as the material of the optically isotropic raw material film prepared in the first step, it can be the same as the crystalline resin described in the first embodiment. However, the crystallinity of the crystalline polymer contained in the raw material film is preferably small. The specific crystallinity is preferably less than 10%, more preferably less than 5%, and particularly preferably less than 3%. When the crystallinity of the crystalline polymer contained in the raw material film before contact with the organic solvent is low, a large number of crystalline polymer molecules can be oriented in the thickness direction by contact with the organic solvent, so the NZ coefficient can be adjusted in a wide range.
[0105] The raw material film is an optically isotropic resin film. That is, the raw material film is a film with a small birefringence Re / d in the in-plane direction and a small absolute value of birefringence |Rth / d| in the thickness direction. Specifically, the birefringence Re / d in the in-plane direction of the raw material film is usually less than 1.0×10 -3 , preferably less than 0.5×10 -3 , more preferably less than 0.3×10 -3 In addition, the absolute value of birefringence in the thickness direction of the raw film |Rth / d| is usually less than 1.0×10 -3 , preferably less than 0.5×10 -3 , more preferably less than 0.3×10 -3. Having optical isotropy like this means that the molecular orientation of the crystalline polymer contained in the raw material film is low and is essentially in a non-oriented state. When such an optically isotropic resin film is used as a raw material film, it is not necessary to precisely control the optical properties of the raw material film, and thus, it is not necessary to precisely control the molecular orientation of the crystalline polymer, so the manufacturing method of the phase difference film can be simplified. Furthermore, when an optically isotropic resin film is used as a raw material film, a phase difference film with a small haze can usually be obtained.
[0106] The raw material film preferably has a small content of organic solvent, and more preferably contains no organic solvent. The ratio of the organic solvent contained in the raw material film to 100% by weight of the raw material film (solvent content) is preferably 1% or less, more preferably 0.5% or less, particularly preferably 0.1% or less, and ideally 0.0%. By reducing the amount of organic solvent contained in the raw material film before contact with the organic solvent, a large number of crystalline polymer molecules can be oriented in the thickness direction by contact with the organic solvent, so that the NZ coefficient can be adjusted in a wide range.
[0107] The solvent content of the raw material film can be measured by density.
[0108] The haze of the raw material film is preferably less than 1.0%, preferably less than 0.8%, more preferably less than 0.5%, and ideally 0.0%. The smaller the haze of the raw material film, the easier it is to reduce the haze of the obtained retardation film.
[0109] The thickness of the raw material film is preferably set according to the thickness of the phase difference film to be manufactured. Usually, by contacting with an organic solvent in the second step, the thickness will become larger. On the other hand, in the case of stretching in the third step, the thickness will become smaller by the stretching. Therefore, the thickness of the raw material film can also be set by considering the change of thickness in the step after the second step as described above.
[0110] The raw material film may be a single film, but is preferably a long film. By using a long raw material film, the retardation film can be continuously produced by a roll-to-roll method, so the productivity of the retardation film can be effectively improved.
[0111] As the manufacturing method of the raw material film, from the aspect of obtaining a raw material film containing no organic solvent, preferred are resin molding methods such as injection molding, extrusion molding, compression molding, inflation molding, blow molding, calendar molding, injection molding, and compression molding. Among these, from the aspect of easy thickness control, preferred is extrusion molding.
[0112] The manufacturing conditions of the extrusion molding method are preferably as follows. The barrel temperature (molten resin temperature) is preferably above Tm, more preferably above "Tm+20°C", preferably below "Tm+100°C", and more preferably below "Tm+50°C". In addition, the cooling body that the molten resin extruded into a film initially contacts is not particularly limited, and a casting roll is usually used. The casting roll temperature is preferably above "Tg-50°C", preferably below "Tg+70°C", and more preferably below "Tg+40°C". Furthermore, the cooling roll temperature is preferably above "Tg-70°C", more preferably above "Tg-50°C", preferably below "Tg+60°C", and more preferably below "Tg+30°C". When a raw material film is manufactured under such conditions, a raw material film with a thickness of 1μm to 1mm can be easily manufactured. Here, "Tm" represents the melting point of a crystalline polymer, and "Tg" represents the glass transition temperature of a crystalline polymer.
[0113] [9. Second step: contact between resin film and organic solvent]
[0114] In the second step, the resin film as the raw material film prepared in the first step is brought into contact with an organic solvent. As the organic solvent, a solvent that can penetrate into the resin film without dissolving the crystalline polymer contained in the resin film can be used, and examples thereof include hydrocarbon solvents such as toluene, limonene, and decalin; and carbon disulfide. The type of the organic solvent may be one, or two or more.
[0115] The contact method between the resin film and the organic solvent is arbitrary. Examples of the contact method include: a spray method in which the organic solvent is sprayed on the resin film; a coating method in which the organic solvent is applied to the resin film; an immersion method in which the resin film is immersed in the organic solvent, etc. Among them, the immersion method is preferred because it is easy to carry out continuous contact.
[0116] The temperature of the organic solvent in contact with the resin film is arbitrary within the range in which the organic solvent can maintain a liquid state, and can be set within the range of not less than the melting point and not more than the boiling point of the organic solvent.
[0117] The time for the resin film to contact with the organic solvent is not particularly specified, preferably more than 0.5 seconds, more preferably more than 1.0 seconds, particularly preferably more than 5.0 seconds, preferably less than 120 seconds, more preferably less than 80 seconds, and particularly preferably less than 60 seconds. In the case where the contact time is more than the lower limit of the above range, the adjustment of the NZ coefficient by contact with the organic solvent can be effectively performed. On the other hand, there is a tendency that the adjustment amount of the NZ coefficient will not change too much even if the immersion time is extended. Thus, in the case where the contact time is less than the upper limit of the above range, the productivity can be improved without damaging the quality of the phase difference film.
[0118] The contact with the organic solvent in the second step changes the birefringence Rth / d in the thickness direction of the resin film. Thus, the NZ coefficient can be adjusted to obtain an NZ coefficient of less than 1.0. The change in the birefringence Rth / d in the thickness direction of the resin film caused by the contact with the organic solvent is preferably 1.0×10 -3 More preferably, 2.0×10 -3 Above, particularly preferably 5.0×10 -3 Above, preferably 50.0×10 -3 Below, more preferably 30.0×10 -3 Below, particularly preferably 20.0×10 -3 The above-mentioned variation of birefringence Rth / d in the thickness direction indicates the absolute value of variation of birefringence Rth / d in the thickness direction.
[0119] The in-plane birefringence Re / d of the resin film may or may not change due to contact with the organic solvent. From the viewpoint of simply controlling the in-plane retardation Re of the phase difference film, it is preferred that the change in the in-plane birefringence Re / d of the resin film due to contact with the organic solvent is small, and more preferably no change occurs. The change in the in-plane birefringence Re / d of the resin film due to contact with the organic solvent is preferably 0.0×10 -3 ~2.0×10 -3 , more preferably 0.0×10 -3 ~1.0×10 -3 , particularly preferably 0.0×10 -3 ~0.5×10 -3 The above-mentioned amount of change in the birefringence Re / d in the in-plane direction represents the absolute value of the change in the birefringence Re / d in the in-plane direction.
[0120] The organic solvent in contact with the resin film will penetrate into the resin film, and thus, in the second step, the thickness of the resin film will generally increase. The lower limit of the rate of change of the thickness of the resin film at this time can be, for example, 10% or more, 20% or more, or 30% or more. In addition, the upper limit of the rate of change of the thickness can be, for example, 80% or less, 50% or less, or 40% or less. The rate of change of the thickness of the above-mentioned resin film refers to the ratio obtained by dividing the change in the thickness of the resin film by the thickness of the raw film (i.e., the resin film before contact with the organic solvent).
[0121] As described above, the second step changes the birefringence Rth / d in the thickness direction of the resin film. Therefore, when a resin film having desired optical properties is obtained by changing the birefringence Rth / d in the thickness direction caused by the second step, the resin film can be obtained as a phase difference film.
[0122] In the production method of the second embodiment, the resin film after the second step may be further subjected to an arbitrary step.
[0123] [10. Third step: stretching of resin film]
[0124] In the method for manufacturing a phase difference film of the second embodiment of the present invention, a third step of stretching the resin film may be included after the second step. By stretching, the molecules of the crystalline polymer contained in the resin film can be oriented along the direction corresponding to the stretching direction. Thus, according to the third step, the optical properties such as the birefringence Re / d in the in-plane direction, the in-plane delay Re, the birefringence Rth / d in the thickness direction, the delay Rth in the thickness direction, the NZ coefficient, and the thickness d of the resin film can be adjusted.
[0125] There is no limitation on the stretching direction, and examples thereof include the length direction, the width direction, and the oblique direction. Here, the oblique direction refers to a direction that is neither parallel nor perpendicular to the width direction in the direction perpendicular to the thickness direction. In addition, the stretching direction may be one direction or two or more directions. Thus, as a stretching method, examples thereof include: a method of uniaxially stretching a resin film in the length direction (longitudinal uniaxial stretching method), a method of uniaxially stretching a resin film in the width direction (transverse uniaxial stretching method), and other uniaxial stretching methods; a biaxial stretching method in which a resin film is stretched in the length direction and in the width direction at the same time, a biaxial stretching method in which a resin film is stretched in one direction in the length direction and in the width direction and then stretched in another direction; a method of stretching a resin film in an oblique direction (oblique stretching method), and the like.
[0126] The stretching ratio is preferably more than 1.1 times, more preferably more than 1.2 times, preferably less than 20.0 times, more preferably less than 10.0 times, further preferably less than 5.0 times, and particularly preferably less than 2.0 times. The specific stretching ratio is preferably appropriately set according to the optical properties, thickness, strength and other factors of the phase difference film to be manufactured. In the case where the stretching ratio is more than the lower limit of the above range, it is possible to make the birefringence change greatly by stretching. In addition, in the case where the stretching ratio is less than the upper limit of the above range, it is possible to easily control the direction of the slow axis, or it is possible to effectively suppress the fracture of the resin film.
[0127] The stretching temperature is preferably above "Tg+5°C", more preferably above "Tg+10°C", preferably below "Tg+100°C", and more preferably below "Tg+90°C". Here, "Tg" represents the glass transition temperature of the crystalline polymer. When the stretching temperature is above the lower limit of the above range, the resin film can be sufficiently softened and stretched uniformly. In addition, when the stretching temperature is below the upper limit of the above range, the resin film can be suppressed from solidifying as the crystallization of the crystalline polymer proceeds, so that stretching can be carried out smoothly, and large birefringence can be generated by stretching. Furthermore, the transparency can usually be improved by reducing the haze of the resulting resin film.
[0128] By implementing the above-mentioned stretching treatment, a stretched film as a stretched resin film can be obtained. As described above, by the stretching in the third step, the birefringence can be changed, and therefore, the NZ coefficient can be adjusted. Thus, in the case of obtaining a resin film as a stretched film having desired optical properties by stretching in the third step, the resin film can be obtained as a phase difference film.
[0129] [11. Fourth step: heat treatment of resin film]
[0130] In the method for manufacturing a phase difference film of the second embodiment of the present invention, a fourth step of heat treating the resin film may be included after the second step. In the case where the method for manufacturing a phase difference film includes a third step, the fourth step is usually performed after the third step. By heat treatment, the crystallization of the crystalline polymer contained in the resin film can be promoted, thereby improving the orientation of the crystalline polymer. In addition, by heat treatment, the amount of organic solvent contained in the resin film can be reduced. Thus, according to the fourth step, the optical properties of the resin film can be adjusted.
[0131] The heat treatment temperature is usually above the glass transition temperature Tg of the crystalline polymer and below the melting point Tm of the crystalline polymer. More specifically, the heat treatment temperature is preferably above Tg°C, more preferably above "Tg+10°C", preferably below "Tm-20°C", and more preferably below "Tm-40°C". Within the above temperature range, the crystallization of the crystalline polymer can be rapidly promoted while suppressing the generation of white turbidity as the crystallization proceeds.
[0132] The treatment time of the heat treatment is preferably 1 second or longer, more preferably 5 seconds or longer, and is preferably 30 minutes or shorter, more preferably 15 minutes or shorter.
[0133] As described above, the birefringence can be changed by the heat treatment in the fourth step, so the NZ coefficient can be adjusted. Therefore, when a resin film having desired optical characteristics is obtained by the heat treatment in the fourth step, the resin film can be obtained as a retardation film.
[0134] [12. Other processes]
[0135] The method for producing a retardation film may further include any steps in combination with the above-mentioned steps.
[0136] For example, the method for producing a retardation film may include a step of removing the organic solvent attached to the resin film after the second step. Examples of the method for removing the organic solvent include drying and wiping.
[0137] For another example, the method for manufacturing a phase difference film may include a preheating process before the third process to heat the resin film to the stretching temperature. Typically, the preheating temperature is the same as the stretching temperature, but may also be different. Relative to the stretching temperature T1, the preheating temperature is preferably above T1-10°C, more preferably above T1-5°C, preferably below T1+5°C, and more preferably below T1+2°C. The preheating time is arbitrary and can be preferably more than 1 second, more preferably more than 5 seconds, and preferably less than 60 seconds, more preferably less than 30 seconds.
[0138] When the method for manufacturing the phase difference film includes the third step or the fourth step, the resin film after these steps will contain residual stress. Therefore, the method for manufacturing the phase difference film may include, for example, a process of performing a relaxation treatment to remove the residual stress by thermally shrinking the resin film. In the relaxation treatment, usually, the resin film is thermally shrunk in an appropriate temperature range while keeping the resin film flat, thereby removing the residual stress.
[0139] According to the above-mentioned manufacturing method, a long strip of raw material film can be used to manufacture a long strip of phase difference film. The manufacturing method of the phase difference film may include the step of winding the long strip of phase difference film manufactured in this way into a roll. The manufacturing method of the phase difference film may also include the step of cutting the long strip of phase difference film into a desired shape.
[0140] [13. Produced phase difference film]
[0141] According to the manufacturing method of the second embodiment of the present invention, birefringence can be adjusted by a simple process of contacting a raw material film with an organic solvent, so a retardation film having a desired NZ coefficient can be easily manufactured. Therefore, according to this manufacturing method, a retardation film having an NZ coefficient of less than 1.0 can be easily obtained.
[0142] In detail, the NZ coefficient of the phase difference film manufactured by the manufacturing method of the second embodiment can be the same as the NZ coefficient of the phase difference film of the first embodiment. Furthermore, for characteristics other than the NZ coefficient, the phase difference film manufactured by the manufacturing method of the second embodiment can also be the same as the phase difference film of the first embodiment. Thus, in the phase difference film manufactured by the manufacturing method of the second embodiment, the crystalline resin contained in the phase difference film; the haze of the phase difference film; the amount of the organic solvent contained in the phase difference film; the delay Re and Rth of the phase difference film; the birefringence Re / d and Rth / d of the phase difference film; the total light transmittance of the phase difference film; the thickness of the phase difference film; and other characteristics can be the same as the phase difference film of the first embodiment.
[0143] [14. Application]
[0144] The retardation film of the first embodiment and the retardation film manufactured by the manufacturing method of the second embodiment can be provided in, for example, a display device. In this case, the retardation film can improve the display quality such as viewing angle, contrast, and image quality of the image displayed by the display device.
[0145] Example
[0146] The present invention will be described in detail below with reference to the following examples, but the present invention is not limited to the following examples and can be arbitrarily modified within the scope of the claims of the present invention and their equivalents.
[0147] In the following description, "%" and "parts" indicating amounts are based on weight unless otherwise specified. In addition, unless otherwise specified, the operations described below are performed under normal temperature and pressure conditions.
[0148] [Evaluation method]
[0149] (Method for measuring weight average molecular weight Mw and number average molecular weight Mn of polymer)
[0150] The weight average molecular weight Mw and number average molecular weight Mn of the polymer as polystyrene conversion values were measured using a gel permeation chromatography (GPC) system ("HLC-8320" manufactured by Tosoh Corporation). During the measurement, an H-type column (manufactured by Tosoh Corporation) was used as a column, and tetrahydrofuran was used as a solvent. In addition, the temperature during the measurement was 40°C.
[0151] (Method for measuring hydrogenation rate of polymer)
[0152] Using o-dichlorobenzene-d4 as solvent, at 145℃ 1 The hydrogenation rate of the polymer was determined by H-NMR measurement.
[0153] [Measurement method of glass transition temperature Tg and melting point Tm]
[0154] The glass transition temperature Tg and melting point Tm of the polymer were measured as follows. First, the polymer was melted by heating, and the melted polymer was quenched with dry ice. Next, the polymer was used as a test body, and the glass transition temperature Tg and melting point Tm of the polymer were measured using a differential scanning calorimeter (DSC) at a heating rate of 10°C / min (heating mode).
[0155] (Method for determining the ratio of syndiotactic diads in polymer)
[0156] The proportion of syndiotactic diads in the polymer was determined as follows. 4 As solvent, the polymer was decoupled at 200 °C using the inverse-gated decoupling method. 13 C-NMR measurement. 13 In the results of C-NMR measurement, o-dichlorobenzene-d 4 The peak of 127.5 ppm was used as the reference shift, and the signal of 43.35 ppm derived from the isotactic dyad and the signal of 43.43 ppm derived from the syndiotactic dyad were identified. The ratio of syndiotactic dyads in the polymer was determined based on the intensity ratio of these signals.
[0157] (Method for measuring retardation Re, Rth and NZ coefficient of film)
[0158] The in-plane retardation Re, the retardation Rth in the thickness direction, and the NZ coefficient of the film were measured using a phase difference meter ("AxoScan OPMF-1" manufactured by AXOMETRICS Co., Ltd.) The measurement wavelength was 590 nm.
[0159] (Method for measuring film thickness)
[0160] The thickness of the film was measured using a contact thickness gauge (Code No. 543-390 manufactured by MITUTOYO CORPORATION).
[0161] (Method for measuring haze of film)
[0162] The haze of the film was measured using a haze meter ("NDH5000" manufactured by Nippon Denshoku Industries, Ltd.).
[0163] (Method for measuring solvent content of phase difference film)
[0164] The weight of the raw material film (resin film before solvent immersion) used to manufacture the phase difference film as a sample was measured by thermogravimetric analysis (TGA: in a nitrogen atmosphere, a heating rate of 10°C / min, 30°C to 300°C). The weight W of the raw material film at 30°C was used. O (30℃) minus the weight of the raw film at 300℃ W O (300°C), calculate the weight loss ΔW of the raw material film at 300°C O The raw material films used in the examples and comparative examples described below are produced by melt extrusion and therefore do not contain a solvent. Therefore, the weight loss ΔW of the raw material film is used in the formula (X) described below. O As a reference.
[0165] In addition, the weight of the phase difference film as a sample was measured by thermogravimetric analysis (TGA: in a nitrogen atmosphere, a heating rate of 10°C / min, 30°C to 300°C). The weight W of the phase difference film at 30°C was used. R (30°C) minus the weight of the retardation film at 300°C W R (300°C), calculate the weight loss ΔW of the retardation film at 300°C R .
[0166] According to the following formula (X), the weight loss ΔW of the raw material film at 300°C is: O and the weight reduction ΔW of the retardation film at 300°C R The solvent content of the retardation film was calculated.
[0167] Solvent content (%) = {(ΔW R -ΔW O ) / W R (30℃)}×100(X)
[0168] [Production Example 1. Production of a crystalline resin comprising a hydrogenated product of a ring-opening polymer of dicyclopentadiene]
[0169] After the metal pressure-resistant reactor was fully dried and purged with nitrogen, 154.5 parts of cyclohexane, 42.8 parts of a 70% cyclohexane solution of dicyclopentadiene (endomorph content of 99% or more) (30 parts of dicyclopentadiene) and 1.9 parts of 1-hexene were added to the metal pressure-resistant reactor and heated to 53°C.
[0170] Dissolve 0.014 parts of phenylimide tungsten tetrachloride (tetrahydrofuran) complex in 0.70 parts of toluene to prepare a solution. Add 0.061 parts of 19% diethyl ethoxyaluminum / n-hexane solution to the solution and stir for 10 minutes to prepare a catalyst solution. Add the catalyst solution to a pressure-resistant reactor to initiate a ring-opening polymerization reaction. Then, keep the reaction at 53°C for 4 hours to obtain a solution of a ring-opening polymer of dicyclopentadiene. The number average molecular weight (Mn) and weight average molecular weight (Mw) of the obtained ring-opening polymer of dicyclopentadiene are 8750 and 28100, respectively, and the molecular weight distribution (Mw / Mn) obtained therefrom is 3.21.
[0171] 0.037 parts of 1,2-ethylene glycol as a terminator was added to 200 parts of the obtained solution of the ring-opening polymer of dicyclopentadiene, and the mixture was heated to 60°C and stirred for 1 hour to terminate the polymerization reaction. 1 part of a hydrotalcite-like compound (Kyoward (registered trademark) 2000 manufactured by Kyowa Chemical Industry Co., Ltd.) was added thereto, heated to 60°C, and stirred for 1 hour. Then, 0.4 parts of a filter aid (Radiolite (registered trademark) #1500 manufactured by Showa Chemical Industry Co., Ltd.) was added, and the adsorbent and the solution were filtered and separated using a polypropylene (PP) folded cartridge filter (TCP-HX manufactured by ADVANTEC Toyo Co., Ltd.).
[0172] 100 parts of cyclohexane were added to 200 parts of the filtered solution of the ring-opening polymer of dicyclopentadiene (polymer amount: 30 parts), and 0.0043 parts of tris(triphenylphosphine)carbonylruthenium hydrochloride were added, and a hydrogenation reaction was carried out for 4 hours under the conditions of a hydrogen pressure of 6 MPa and 180° C. Thus, a reaction solution containing a hydrogenated product of the ring-opening polymer of dicyclopentadiene was obtained. In the reaction solution, the hydrogenated product was precipitated to form a slurry solution.
[0173] The hydride contained in the reaction solution was separated from the solution using a centrifugal separator and dried under reduced pressure at 60° C. for 24 hours to obtain 28.5 parts of a crystalline hydrogenated ring-opening polymer of dicyclopentadiene. The hydrogenated product had a hydrogenation rate of 99% or more, a glass transition temperature Tg of 93° C., a melting point (Tm) of 262° C., and a syndiotactic diad ratio of 89%.
[0174] 1.1 parts of an antioxidant (tetrakis [methylene-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl) propionate] methane, manufactured by BASF Japan Co., Ltd., "Irganox (registered trademark) 1010") were mixed with 100 parts of the obtained hydrogenated product of the ring-opening polymer of dicyclopentadiene, and then added to a twin-screw extruder having four die holes with an inner diameter of 3 mm (product name "TEM-37B", manufactured by Toshiba Machine Co., Ltd.). The mixture of the hydrogenated product of the ring-opening polymer of dicyclopentadiene and the antioxidant was formed into a strand by hot melt extrusion molding, and then chopped in a wire cutter to obtain a crystalline resin in the form of particles. The operating conditions of the above-mentioned twin-screw extruder are as follows.
[0175] ·Cylinder set temperature = 270℃~280℃
[0176] Die head set temperature = 250℃
[0177] Screw speed = 145 rpm
[0178] [Example 1]
[0179] (1-1. First step: production of raw material film)
[0180] The crystalline resin produced in Example 1 was formed using a hot melt extrusion film forming machine with a T-die ("Measuring Extruder Type Me-20 / 2800V3" manufactured by Optical Control Systems Co., Ltd.), and wound into a roll at a speed of 1.5 m / min to obtain a long resin film (thickness 50 μm) as a raw material film with a width of about 120 mm. The operating conditions of the above-mentioned film forming machine are as follows.
[0181] ·Cylinder set temperature = 280℃~300℃
[0182] Die temperature = 270°C
[0183] Screw speed = 30rpm
[0184] Casting roll temperature = 80°C
[0185] (1-2. Second step: contact between raw material film and processing solvent)
[0186] The resin film was cut into 100 mm × 100 mm. The delay was measured using a phase difference meter, and the result was that the in-plane delay Re = 5 nm and the delay in the thickness direction Rth = 6 nm. As described above, the resin film was manufactured by hot melt extrusion at a high temperature (280°C to 300°C), so it can be considered that the resin film does not contain a solvent, so its solvent content is 0.0%.
[0187] The barrel was filled with toluene as a processing solvent, and the resin film was immersed in the toluene for 5 seconds. Then, the resin film was taken out from the toluene and the surface was wiped with gauze. The obtained resin film was evaluated as a phase difference film according to the above method. As a result, the in-plane delay Re = 9nm, the delay in the thickness direction Rth = -575nm, the thickness was 64μm, and the haze Hz was 0.4%.
[0188] [Example 2]
[0189] In the above step (1-1), the thickness of the resin film as the raw material film was changed to 20 μm by adjusting the speed (line speed) at which the film was wound into a roll.
[0190] In addition, in the above step (1-2), the time for immersing the resin film in the treatment solvent (here, toluene) was changed to 1 second.
[0191] The retardation film was produced and evaluated in the same manner as in Example 1 except for the above matters.
[0192] [Example 3]
[0193] In the above step (1-1), the thickness of the resin film as the raw material film was changed to 100 μm by adjusting the speed (line speed) at which the film was wound into a roll.
[0194] In addition, in the above step (1-2), the time for immersing the resin film in the treatment solvent (here, toluene) was changed to 60 seconds.
[0195] The retardation film was produced and evaluated in the same manner as in Example 1 except for the above matters.
[0196] [Example 4]
[0197] Prepare a stretching device ("SDR-562Z" manufactured by ETO Corporation). The stretching device has a clamp and an oven that can hold the ends of a rectangular resin film. Five clamps are provided on each side of the resin film, and one is provided at each vertex of the resin film, a total of 24 clamps are provided, and the resin film can be stretched by moving these clamps. In addition, two ovens are provided, and the stretching temperature and the heat treatment temperature can be set separately. Furthermore, in the above-mentioned stretching device, the resin film can be moved from one oven to the other oven in a state of being held by a clamp.
[0198] In the same manner as in Example 1, a resin film as a raw material film was produced, and the resin film was brought into contact with toluene.
[0199] The resin film after contact with toluene is installed in the above-mentioned stretching device, and the resin film is treated at a preheating temperature of 110°C for 10 seconds. Then, the resin film is stretched at a stretching temperature of 110°C with a longitudinal stretching ratio of 1, a transverse stretching ratio of 1.5, and a stretching speed of 1.5 times / 10 seconds. The above-mentioned "longitudinal stretching ratio" represents the stretching ratio in the direction consistent with the length direction of the long strip raw film, and the "transverse stretching ratio" represents the stretching ratio in the direction consistent with the width direction of the long strip raw film. Thus, a stretched film as a stretched resin film is obtained. The stretched film is evaluated as a phase difference film according to the above method. As a result, the in-plane delay Re=347nm, the delay in the thickness direction Rth=-12nm, the thickness is 47μm, and the haze Hz is 0.4%.
[0200] [Example 5]
[0201] The thickness of the resin film as the raw material film was changed to 35 μm by adjusting the speed (line speed) of winding the film into a roll. A retardation film was produced and evaluated in the same manner as in Example 4 except for the above matters.
[0202] In Example 5, the thickness of the resin film obtained after contacting with toluene (resin film before stretching) was 47 μm, and the retardation Rth in the thickness direction was −420 nm.
[0203] [Example 6]
[0204] When the resin film was stretched using the stretching device, the transverse stretching ratio was changed to 1.3 times. A retardation film was produced and evaluated in the same manner as in Example 4 except for the above matters.
[0205] [Example 7]
[0206] In the same manner as in Example 4, a resin film as a raw material film was produced, the resin film was brought into contact with toluene, and the resin film was stretched.
[0207] The stretched film, which is a resin film to be stretched, was moved to an oven for heat treatment in a state held by a clamp and heat treated at a treatment temperature of 170°C for 20 seconds. The stretched film after heat treatment was evaluated as a phase difference film according to the above method. The results showed that the in-plane delay Re = 378nm, the delay in the thickness direction Rth = -10nm, the thickness was 44μm, and the haze Hz was 0.4%.
[0208] [Example 8]
[0209] The treatment time of the heat treatment was changed to 10 minutes. A retardation film was produced and evaluated in the same manner as in Example 7 except for the above matters.
[0210] [Example 9]
[0211] By adjusting the speed (line speed) of winding the film into a roll, the thickness of the resin film as the raw material film was changed to 30 μm. In addition, when the resin film was stretched using a stretching device, the transverse stretching ratio was changed to 1.7 times. In addition to the above matters, the retardation film was manufactured and evaluated in the same manner as in Example 4.
[0212] In Example 9, the thickness of the resin film obtained after contacting with toluene (resin film before stretching) was 41 μm, and the retardation Rth in the thickness direction was −370 nm.
[0213] [Example 10]
[0214] By adjusting the speed (line speed) of winding the film into a roll, the thickness of the resin film as the raw material film was changed to 33 μm. In addition, when the resin film was stretched using a stretching device, the transverse stretching ratio was changed to 1.4 times. In addition to the above matters, the same method as Example 4 was used to manufacture and evaluate the phase difference film.
[0215] In Example 10, the thickness of the resin film obtained after contacting with toluene (resin film before stretching) was 44 μm, and the retardation Rth in the thickness direction was −390 nm.
[0216] [Example 11]
[0217] The type of the treatment solvent was changed from toluene to limonene. A retardation film was produced and evaluated in the same manner as in Example 1 except for the above matters.
[0218] [Example 12]
[0219] The type of the treatment solvent was changed from toluene to decalin. In addition, the time for immersing the resin film in the treatment solvent (here, decalin) was changed to 60 seconds. Except for the above matters, the retardation film was produced and evaluated in the same manner as in Example 1.
[0220] [Comparative Example 1]
[0221] A long strip of resin film is produced by the same method as step (1-1) of Example 1. The obtained resin film is cut into 100 mm × 100 mm. The cut resin film is installed in the above-mentioned stretching device and treated at a preheating temperature of 110°C for 10 seconds. Then, at a stretching temperature of 110°C, the resin film is stretched with a longitudinal stretching ratio of 1 times, a transverse stretching ratio of 1.5 times, and a stretching speed of 1.5 times / 10 seconds. The stretched resin film has an in-plane retardation Re = 62 nm, a thickness retardation Rth = 77 nm, a thickness of 33 μm, and a haze Hz of 0.1%.
[0222] The stretched resin film is used as a raw material film and is brought into contact with toluene as a processing solvent. That is, a bucket is filled with toluene, and the stretched resin film is immersed in the toluene for 5 seconds. Then, the resin film is taken out from the toluene and the surface is wiped with gauze. According to the above method, the obtained resin film is evaluated as a phase difference film.
[0223] [Comparative Example 2]
[0224] A long resin film is produced by the same method as step (1-1) of Example 1. The obtained resin film is cut into 100 mm × 100 mm. The cut resin film is installed in the above-mentioned stretching device and treated at a preheating temperature of 110°C for 10 seconds. Then, at a stretching temperature of 110°C, the resin film is stretched with a longitudinal stretching ratio of 1 times, a transverse stretching ratio of 2 times, and a stretching speed of 1.5 times / 10 seconds. The stretched resin film has an in-plane retardation Re = 91 nm, a thickness retardation Rth = 85 nm, a thickness of 25 μm, and a haze Hz of 0.1%.
[0225] The stretched resin film is used as a raw material film and is brought into contact with toluene as a processing solvent. That is, a bucket is filled with toluene, and the stretched resin film is immersed in the toluene for 5 seconds. Then, the resin film is taken out from the toluene and the surface is wiped with gauze. According to the above method, the obtained resin film is evaluated as a phase difference film.
[0226] [Comparative Example 3]
[0227] A long resin film was produced by the same method as step (1-1) of Example 1. The obtained resin film was cut into 100 mm × 100 mm. Shrink films were attached to both sides of the cut resin film to obtain a multilayer film. The above-mentioned shrink film is a film having the property of shrinking 20% in the longitudinal direction and 25% in the transverse direction at 145°C.
[0228] The multilayer film was mounted on the stretching device and treated at a preheating temperature of 145°C for 5 seconds. Then, the multilayer film was stretched at a stretching temperature of 145°C with a longitudinal stretching ratio of 0.8 times and a transverse stretching ratio of 1.2 times. The shrink film was removed from the stretched multilayer film to obtain a resin film as a phase difference film. The resin film was evaluated according to the above method.
[0229] [result]
[0230] The results of the above-mentioned Examples and Comparative Examples are shown in the following tables. In the following tables, the abbreviations have the following meanings.
[0231] COP: hydrogenated ring-opening polymer of dicyclopentadiene
[0232] d: thickness
[0233] Re: In-plane delay.
[0234] Rth: Retardation in the thickness direction.
[0235] Hz: Haze
[0236] [Table 1]
[0237] [Table 1. Results of Examples 1 to 8]
[0238]
[0239] [Table 2]
[0240] [Table 2. Results of Examples 9 to 13 and Comparative Examples 1 to 3]
[0241]
[0242] [discuss]
[0243] As shown in Comparative Example 3, a film having an NZ coefficient of less than 1.0 can be produced by a manufacturing method combining stretching and shrinking of the film. However, the control of combining stretching and shrinking like this is complicated. Furthermore, the birefringence of the film obtained in Comparative Example 3 is small and cannot be used as a phase difference film. As a result, a phase difference film having an NZ coefficient of less than 1.0 cannot be simply produced.
[0244] In addition, as shown in Comparative Example 2, even when the optically anisotropic raw material film is brought into contact with an organic solvent, a retardation film having an NZ coefficient of less than 1.0 cannot be easily produced. Furthermore, it is considered that the retardation film obtained in Comparative Example 2 has a large haze, and when it is set in a display device, the clarity of the image is poor.
[0245] As shown in Comparative Example 1, in the case of using a raw material film that appropriately controls the orientation of the molecules of the crystalline polymer by appropriately adjusting the optical properties, even if the raw material film has optical anisotropy, it is sometimes possible to produce a phase difference film with an NZ coefficient less than 1.0. However, in Comparative Example 2, which uses an optically anisotropic raw material film as in Comparative Example 1, an NZ coefficient less than 1.0 is not obtained. It can be seen that in the case of using an optically anisotropic raw material film, in order to achieve an NZ coefficient less than 1.0, it is necessary to precisely control the optical properties of the raw material film, and thus, it is necessary to precisely control the orientation of the molecules of the crystalline polymer contained in the raw material film. Therefore, in the case of using an optically anisotropic raw material film, the control is complicated and the simple manufacture of the phase difference film cannot be achieved. In addition, the phase difference film of Comparative Example 1 has a large haze, like the phase difference film of Comparative Example 2.
[0246] In contrast, in the examples, a retardation film having an NZ coefficient of less than 1.0 is obtained by a simple method of contacting an optically isotropic raw material film with an organic solvent. In addition, the haze of the obtained retardation film is sufficiently small. Thus, according to the results of these examples, it can be confirmed that, by the manufacturing method of the present invention, a retardation film having an NZ coefficient of less than 1.0 can be simply manufactured, and the haze of the manufactured retardation film can be made small.
Claims
1. A method for manufacturing a phase difference film, comprising the following steps: In the first step, an optically isotropic resin film formed of a resin including a crystalline polymer is prepared, and In the second step, the resin film is brought into contact with an organic solvent to change the birefringence Rth / d in the thickness direction, thereby adjusting the NZ coefficient of the resin film to less than 1.
0. The amount of change in birefringence Rth / d in the thickness direction of the resin film caused by contact with the organic solvent is 1.0×10 -3 above.
2. The method for producing a phase difference film according to claim 1, wherein: After the second step, a third step of stretching the resin film is included.
3. The method for producing a phase difference film according to claim 1 or 2, wherein: The organic solvent is a hydrocarbon solvent.
4. The method for producing a phase difference film according to claim 1 or 2, wherein: The crystalline polymer contains an alicyclic structure.
5. The method for producing a phase difference film according to claim 1 or 2, wherein: The crystalline polymer is a hydrogenated product of a ring-opening polymer of dicyclopentadiene.
6. A retardation film produced by the method for producing a retardation film according to any one of claims 1 to 5, The phase difference film is formed of a resin including a crystalline polymer. The NZ coefficient of the phase difference film is less than 1.0, and The haze of the phase difference film is less than 1.0%, The crystalline polymer contains an alicyclic structure, The phase difference film contains an organic solvent, The organic solvent is an organic solvent that does not dissolve the resin including the crystalline polymer.
7. The phase difference film according to claim 6, wherein: The NZ coefficient of the retardation film is greater than 0.0 and less than 1.
0.
8. The phase difference film according to claim 6 or 7, wherein: The organic solvent is a hydrocarbon solvent.
9. The phase difference film according to claim 6 or 7, wherein: The crystalline polymer is a hydrogenated product of a ring-opening polymer of dicyclopentadiene.
Citation Information
Patent Citations
Molded styrene-based polymer product and production thereof
JP1990064141A
Method for producing resin film, resin film, and optical film
JP2016026909A
Phase difference film and production method for same
WO2017065222A1
Resin film, barrier film, and electrically conductive film, and production methods therefor
WO2018062067A1
Method for producing optical film, optical film, and image display
CN101930092A